Costed Plan for Scaling Up Nutrition : Nigeria - World Bank (Washington, DC, 2015)
This paper estimates country-specific costs and benefits of scaling up key nutrition investments in Nigeria. Building on the methodology established in the global report scaling up nutrition: what will it cost? Authors first estimate the costs and benefits of a nationwide scale up of ten effective nutrition-specific interventions. This will require an annual public investment of $837 million and would yield enormous benefits: over 8.7 million DALYs and 183,000 lives would be saved annually, while more than 3 million cases of stunting among children under five will be averted. As it is unlikely that the Government of Nigeria or its partners will find the $837 million necessary to reach full national coverage, authors also consider five potential scale-up scenarios based on considerations of burden of stunting, potential for impact, resource requirements and capacity for implementation in Nigeria. Using cost-benefit analyses authors propose scale-up scenarios that represent a compromise between the need to move to full coverage and the constraints imposed by limited resources and capacities. This analysis takes an innovative approach to nutrition costing by not only estimating the costs and benefits of nutrition-specific interventions, but also exploring costs for a selected number of nutrition-sensitive interventions implemented outside of the health sector. We identify and cost four candidate nutrition-sensitive interventions with impact potential in Nigeria, including bio-fortification of cassava, aflatoxin control, school-based deworming, and school-based promotion of good hygiene. Overall, these findings point to a candidate list of nutrition-sensitive approaches that represent a cost-effective approach to reducing child malnutrition in Nigeria. Moving forward, these results are intended to help guide decision makers as they plan future efforts to scale-up action against malnutrition in Nigeria and develop nutrition financing plans that bring to bear resources from the health, social protection, education, and agriculture sectors.